Structure-based identification of bioactive compounds as trace amine-associated receptor 1 agonists for the therapeutic management of major depressive disorder - Abdelbaset Mohamed Elasbali; Ahmed S. Ali; Mohd Adnan; Taj Mohammad; Anas Shamsi; Md. Imtaiyaz Hassan (PLoS ONE, 2025)
The global burden of major depressive disorder (MDD) drives ongoing efforts to develop safer and more targeted treatment strategies. Modern advances have identified trace amine-associated receptor 1 (TAAR1) as a promising non-monoaminergic target with demonstrated efficacy in treating neuropsychiatric conditions, including MDD. Discovering TAAR1 agonists holds promise for modulating neuropsychiatric disorders while potentially reducing the common side effects associated with conventional therapies. This study employed a structure-based virtual screening approach to identify potential TAAR1 agonists from the IMPPAT database, a curated collection of Indian medicinal plant-derived bioactive phytoconstituents. The initial filtering was done on the compounds based on Lipinski’s rule of five, which was followed by molecular docking, PAINS screening, pharmacokinetic evaluation, and bioactivity predictions. Through this integrative screening approach, we discovered two promising phytochemicals, Bianthraquinone and Peimisine, demonstrating strong binding affinities and favorable drug-like properties. Detailed interaction analysis revealed that both compounds formed stable hydrogen bonds, hydrophobic contacts, and π-π stacking interactions with key residues within the TAAR1 binding pocket, contributing to their high binding stability and receptor specificity. All-atom molecular dynamics simulations, MM-PBSA, and essential dynamics analyses affirmed that they were stable and exhibited favorable conformational interactions. These findings highlight the therapeutic potential of naturally derived TAAR1 agonists and support their further exploration as next-generation antidepressants, laying the foundation for future experimental and clinical development.